Bacteria–Molasses Synergy in Heterotrophic Systems: A Sustainable Strategy for Catfish Survival and Water Quality Improvement - Muhammad Iqbal; Zharifa Rasul (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to evaluate the survival of catfish (Clarias gariepinus) in an intensive heterotrophic culture system, focusing on the effects of the system on fish survival, growth, and health. Furthermore, this study aimed to identify environmental factors that support successful cultivation in an intensive heterotrophic system. Methodology: This study used 12 fiber tanks with a funnel-shaped bottom and The study used 12 fiber tanks (250 L) with a density of 20 catfish (± 50 g/tail) and four treatments: feed only, feed+molasses, feed+bacteria, and feed+molasses+bacteria (heterotrophic system), each with three replications. Survival parameters and water quality (temperature, pH, DO, ammonia, nitrite, nitrate, VSS) were measured periodically. Data were analyzed using one-way ANOVA followed by a 5% Duncan test. Main Findings: The analysis results show that the heterotrophic system produces good catfish survival and water quality that supports the growth of catfish. The heterotrophic system is able to increase the survival of catfish in intensive cultivation by up to 80–90%, reduce the concentration of ammonia to 0.98 mg/L, nitrite to 1.06 mg/L, and nitrate, thus producing water quality that is very supportive of the success of intensive cultivation. In addition, the highest volatile suspended solid value was recorded at 0.90 mg/L in the heterotrophic system. Novelty/Originality of this study: This research presents a new approach to intensive catfish to simultaneously improve fish survival and optimize water quality. These findings expand knowledge on nitrogen waste management and provide practical strategies for the development of sustainable aquaculture technologies.